Metabolic Syndrome and Its Determinants in Patients Undergoing Obesity Screening Within the Scope of the Disease Management Platform - Esranur Yayın; Hasan Esad Yayın (International Journal of Clinical Practice)
Conclusion: The significant increases in the rates of overweight and metabolic syndrome have drawn attention in the community. Therefore, family physicians necessitate additional platforms, such as the DMP, to effectively combat metabolic syndrome and overweight, a pivotal initial step in tackling obesity.